(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Customer satisfaction is a key performance indicator in the oil industry of Kenya which is determined by branding strategies and the quality of the service. Rebranding tools to increase customer experience and loyalty have become more and more popular among oil marketing companies. This paper has specifically looked at how brand refresh strategies have influenced customer satisfaction in the oil industry within Kenya. Brand Equity theory was used as the guiding theory. The research design adopted was descriptive research design that focused on station managers of Rubis Energy, Vivo Energy, and TotalEnergies in Kenya. There were 270 station managers which were the target population and a census approach was used. The major data collection tools were structured questionnaires. Pilot study was done on 27 station managers of Ola Energy and Be Energy to determine the validity and reliability of the research tool. Findings produced Cronbachs Alpha coefficients of more than 0.80 in all constructs with brand refresh yielding 0.84 and a total reliability coefficient of 0.86 indicating high internal consistency. Two hundred and one out of the 270 questionnaires distributed were returned and completed thus giving a response rate of 78.15. Data was examined through descriptive, as well as inferential statistics with the help of SPSS version 31. Results showed that brand refresh was strongly and statistically significant related to customer satisfaction (R = 0.624, 9 = 0.553, p < 0.05). The research found that regular brand refresh activities including new logos, professional branding images and better station surroundings can make a huge contribution to customer satisfaction. It advises that the oil marketing firms should always take initiative to create brand refresh in line with customer expectations in order to remain competitive, build loyalty and enhance customer retention. The study helps in policy formulation, managerial-decision making, and literature on branding, service quality, and customer satisfaction in the oil industry.